What Doesn't Kill You Makes You Poorer : Adult Wages and the Early-Life Disease Environment in India - Lawson, Nicholas (World Bank Group, Washington, DC, 2014)
A growing literature documents links between early-life health and human capital, and between human capital and adult wages. Although most of this literature has focused on developed countries, economists have hypothesized that effects of early-life health on adult economic outcomes could be even greater in developing countries. This paper asks whether the early-life disease environment in India influences adult economic wages. The paper uses two measures of early-life disease environment to investigate this question: infant mortality rates and open defecation. A district-level differences-in-differences strategy is used to show that men born in district-years with lower infant mortality and better sanitation earned plausibly higher wages in their 20s and 30s. The effect estimates are applied to calculate the fiscal and welfare consequences of the disease environment, which are considerable. In particular, eliminating open defecation would increase tax revenue by enough to offset completely a cost to the government of over \$400 per household that stops defecating in the open. A fiscally neutral elimination of open defecation in India would increase the net present value of lifetime wages by more than \$1,800 for an average male worker born today. These large economic benefits ignore any other benefits of improved health or reduced mortality. The result suggests that the disease environment could have important effects on developing-country economic outcomes.